DIVERSITY OF ACTINOMYCETES FROM EKA KARYA BOTANICAL GARDEN, BALI - Shanti Ratnakomala; Puspita Lisdiyanti; Nita Rosalinda Prayitno; Evi Triana; Yulin Lestari; Ratih Dwi Hastuti; Yantyati Widyastuti; Misa Otoguro; Katsuhiko Ando; Endang Sukara (BIOTROPIA, 2016)
A total of 29 actinomycetes strains were isolated and identified by full sequence analysis of the 16S rRNA gene. Samples were collected from Bali Island, Indonesia, including 18 soil and 20 leaf litter samples from Eka Karya Botanical Garden. Two isolation methods were used in this study: SDS-extract (SY) and Rehydration-Centrifugation (RC). Based on 16S rRNA gene analysis, the isolated actinomycetes were grouped into two genera. Molecular analysis of 16S rRNA gene similarities showed that the actinomycetes isolated from Eka Karya Botanical Garden were of diverse origin. Analysis of soil samples resulted in 144 isolates belonging to 24 genera and more than 87 species, with Streptomyces being the dominant genus. This was followed by Actinoplanes (25 isolates, 17%). From leaf litter samples, 85 isolates were obtained, belonging to 9 genera and more than 41 species. The most dominant genus was Catenuloplanes (42 isolates, 49%), followed by Actinoplanes (16 isolates, 19%).